The Influence of Government Regulation No. 51 of 2009 concerning Pharmaceutical Practice on Discipline and its Implications on the Performance of Pharmacists in the East Jakarta Region - Nugraha, Nunu; Sampurno, Sampurno; Djoharsjah, T. (PT Mattawang Mediatama Solution, 2024)
Pharmaceutical practices by pharmacists require work discipline comply with obligations also avoid the prohibitions prescribed in regulations. The pharmacist's discipline deals with the various elements of management directly related to pharmacist performance. This study aims to determine the effect of Government Regulation No. 51 year 2009 regarding pharmaceutical practice of discipline and its implications on pharmacists’ performance in East Jakarta. Using population of pharmacist in East Jakarta as a sample from 200 respondents, the results of Implementation of Government Regulation No. 51 of 2009 on implementation pharmaceutical conducted by pharmacists has been done effectively by 69.50%. Discipline of the Apothecary has been done well by Pharmacists and Pharmacy Manager at 69.58%. Pharmacists and Pharmacy Managers already provide optimal performance for 70.03%. Implementation of Government Regulation No. 51 Year 2009 on Pharmaceutical Works has a positive influence on Pharmacist Discipline and Pharmacy Manager for 0.93 indicating that the relationship is very strong. The pharmacist discipline proved to have a positive effect on Pharmacists' and Pharmacist's Pharmacy Performance of 0.84 indicating that the relationship is very strong.